2012
DOI: 10.1021/pr300218h
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Treatment of Acute Paranoid Schizophrenia Patients with Olanzapine Results in Altered Glycosylation of Serum Glycoproteins

Abstract: Atypical antipsychotic drugs, such as olanzapine, have been shown to alleviate the positive, negative and, to a lesser degree, the cognitive symptoms of schizophrenia in many patients. However, the detailed mechanisms of action of these drugs have yet to be elucidated. We have carried out the first investigation aimed at evaluating the effects of olanzapine treatment on the glycosylation of serum proteins in schizophrenia patients. Olanzapine treatment resulted in increased levels of a disialylated biantennary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…The effects of antipsychotic medication on N-glycosylation in brain tissue have not been previously reported. However, olanzapine treatment has been shown to affect the abundance of some N-linked glycoforms in both serum and cerebrospinal fluid in early-stage, antipsychotic naive patients (Telford et al, 2012). We performed post-hoc analyses to assess possible medication effects on our results, finding no indication that antipsychotic treatment affected the outcomes of these experiments.…”
Section: Discussionmentioning
confidence: 96%
“…The effects of antipsychotic medication on N-glycosylation in brain tissue have not been previously reported. However, olanzapine treatment has been shown to affect the abundance of some N-linked glycoforms in both serum and cerebrospinal fluid in early-stage, antipsychotic naive patients (Telford et al, 2012). We performed post-hoc analyses to assess possible medication effects on our results, finding no indication that antipsychotic treatment affected the outcomes of these experiments.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in schizophrenia brain have identified abnormalities of multiple glycosylation pathways (Bauer et al, 2010; Berretta, 2012; Berretta et al, 2015; Ikemoto, 2014; Mueller et al, 2014; Narayan et al, 2009; Pantazopoulos et al, 2013; Stanta et al, 2010; Telford et al, 2012; Tucholski et al, 2013b, 2013a) and dysregulated expression of glycosylation enzymes has been proposed as a possible mechanism underlying these deficits. Our current report builds on the prior finding of altered transcript levels of CAzymes in schizophrenia cortex by assessing the protein expression of a subset of these, fucosyltransferases and fucosidases.…”
Section: Discussionmentioning
confidence: 99%
“…Reports examining glycan expression in serum and cerebrospinal fluid of schizophrenia patients in early stages of the disorder have found differences in the degree of glycan branching and levels of glycan galactosylation and sialylation following 6 weeks of antipsychotic treatment (Telford et al, 2012). Although specific differences in fucosylation were not observed in those studies, to address the possibility that administration of neuroleptics may result in dysfucosylation in elderly patient brain which may not be reflected in peripheral fluids in earlier stages of the disorder, we evaluated the expression of POFUT2 and FUT8, as well as AAL binding in cortical tissue of rats receiving long-term chronic antipsychotic administration.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant findings that correlate various human diseases with changes in protein glycosylation , the associations that have been found between protein glycosylation and the use of drugs, hormones, and steroids , and the need for detailed characterizations of functionally active glycosylated proteins and biotherapeutics , have stimulated the community for tackling progressively more sophisticated approaches for deciphering the complex glycoproteome.…”
Section: Analysis Of Protein N‐glycosylation By Esi‐msmentioning
confidence: 99%